1996
DOI: 10.1111/j.1472-8206.1996.tb00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of indomethacin on the haemodynamic effects of lipopolysaccharide in rats

Abstract: This study was undertaken to evaluate the influence of the cyclooxygenase inhibitor indomethacin on the time course of the haemodynamic effects of lipopolysaccharide (LPS) intravenous infusion (10 mg.kg-1.h-1) in anaesthetized rats. LPS infusion produced a rapid (within 10 min) and prolonged (over the 90 min observation period) fall in mean arterial blood pressure (MABP) and a decrease in the pressor responses to noradrenaline (NA, 0.1, 0.3 and 1 microgram.kg-1, intravenously [i.v.]) elicited 60 and 90 min aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The beneficial effects of indomethacin are correlated with decreased levels of nitrite and prostaglandins in biological fluids from endotoxemic rats (Futaki et al , 1997). Indomethacin has also shown to abolish or significantly attenuate the decrease in blood pressure (Fatehi-Hassanabad et al , 1996) or have no significant effect on blood pressure in endotoxemic rats (Pique et al , 1988; Vayssettes-Courchay et al , 2002). Vasoconstriction and increased blood pressure after systemic inhibition of NOS results not only from withdrawal of vasodilator NO, but from increased activity of the vasoconstrictor systems, including sympathetic nervous and renin-angiotensin systems, and production of endothelins and 20-hydroxyeicosatetraenoic acid (20-HETE), an arachidonic acid metabolite derived via cytochrome P450 (CYP) (Fleming, 2001; Roman, 2002; Zatz and Baylis, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of indomethacin are correlated with decreased levels of nitrite and prostaglandins in biological fluids from endotoxemic rats (Futaki et al , 1997). Indomethacin has also shown to abolish or significantly attenuate the decrease in blood pressure (Fatehi-Hassanabad et al , 1996) or have no significant effect on blood pressure in endotoxemic rats (Pique et al , 1988; Vayssettes-Courchay et al , 2002). Vasoconstriction and increased blood pressure after systemic inhibition of NOS results not only from withdrawal of vasodilator NO, but from increased activity of the vasoconstrictor systems, including sympathetic nervous and renin-angiotensin systems, and production of endothelins and 20-hydroxyeicosatetraenoic acid (20-HETE), an arachidonic acid metabolite derived via cytochrome P450 (CYP) (Fleming, 2001; Roman, 2002; Zatz and Baylis, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Endotoxin is known to induce the expression of other enzymes, including cyclo‐oxygenase (COX‐2) ( Bishop‐Bailey et al ., 1997 ) suggesting that additional mechanisms are likely to contribute to endotoxin‐induced changes in vascular reactivity. For example, increased prostanoid production and enhanced potassium channel activity have been reported to contribute to the development of hypotension and vascular hyporeactivity ( Wu et al ., 1995b ; Fatehi‐Hassanabad et al ., 1996 ; Clapp & Tinker, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of indomethacin are correlated with decreased levels of nitrite and prostanoids in biological fluids from endotoxaemic rats [40]. Indomethacin also abolishes or significantly attenuates the decrease in mean arterial pressure (MAP) [41] or has no significant effect on blood pressure in endotoxaemic rats [42]. Our previous studies suggested that dual inhibition of iNOS and COX by indomethacin restores MAP presumably because of increased production of 20‐HETE derived from AA by CYP4A in endotoxaemic rats [32].…”
mentioning
confidence: 99%